Komunikasi Resiko Dalam Kebijakan Pengelolaan Sampah Perspektif Regulasi dan Sosialisasi Peraturan Bupati Deli Serdang No. 6 Tahun 2025 - Bakhrul Khair Amal (Medan Resource Center, 2025)
This study examines the application of risk communication in the socialization process of Deli Serdang Regent Regulation No. 6 of 2025 on waste management, a policy that emerges amid increasing environmental and public health risks in the region. Using a descriptive qualitative design with a case study approach, the research involves 12 informants consisting of government officials, community leaders, and waste-management stakeholders. Data were collected through in-depth interviews, participatory observation, and document analysis, and were analyzed using thematic analysis to identify patterns in message delivery, actor involvement, and audience response. The findings show that although the regulation mandates collective responsibility, its communication strategy remains predominantly one-way and has not fully articulated key risk dimensions—particularly localized environmental and health implications. One notable finding is the absence of mechanisms for two-way feedback, which reduces community readiness to adopt waste-sorting practices. This article contributes to risk communication scholarship by demonstrating how regulatory socialization in decentralized regions must integrate contextualized risk framing and community-based dialogic models to increase policy acceptance. Strengthening message clarity, enhancing source credibility, and utilizing adaptive digital media are therefore crucial to improving public understanding and fostering collective participation in waste management.